Traffic Congestion: Shift from Private Car to Public Transportation - Layth Riyadh Abdulrazzaq; Mohammed Naeem Abdulkareem; Muhamad Razuhanafi Mat Yazid; Muhamad Nazri Borhan; Mina Salah Mahdi (Salehan Institute of Higher Education, 2020)
Private Cars (PC) are becoming the most common way to travel daily. This is one of the effects of poor access to Public Transport (PT). As a result, increase air pollution, traffic congestion, noise, accidents. This study aims to develop a modal shift model for car users to shift to PT and determine the factors that effects the performance of the mode of transportation. A survey of 384 of PT users was conducted in Kajang city, Malaysia. Data were processed by SPSS software. A binary logit model has been used for three different lines (car, train and bus). The explanatory factors that looked at two models include trip distances, a trip rate per day, trip time, gender, age, and occupation, which are important variables. Mode Choice Model (Car vs Bus) show the travel time and distance travelled are significant factors to increase the use of public buses and reduce dependence on the car. While in Model (Car vs Train), the travel time is an important variable that effects of the switching decision between car and train. Younger people are more likely to switch in both models. Improve some factors like reliability in public transport services and change some fundamental policy could be the most effective measures for shifting from PC to PT.